Possible changes in transport conception of international and long-distance railway connections relating the construction of new high-speed railway lines in the Czech Republic - Pavel Purkart; David Vodák; Tomáš Javořík; Martin Jacura (Acta Polytechnica CTU Proceedings)
The aim of this article is to deal with the issue of high-speed railway lines (HSL) in the Czech Republic in response to the Fast connections conception ("Rychlá spojení" in Czech, abbreviation "RS"). Currently the RS1, RS2 and RS4 projects are the most watched during the preparation of the HSL network construction. The authors would like to focus on this issue from the wider point of view and to assess possible impact on the current lines of long-distance trains, the location of graphical timetable nodes and the way of the transport service on the area of the state.